PROBLMS OF CHILDHOOD AND EDUCATION IN CH.DICKENS’ WORK - G’ulomova Shahlo Mansur qizi; Khamitov Eldorbek Erkin o‘g‘li (TADQIQOTLAR.UZ, 2024)
ABSTRACT Charles Dickens’ works, especially those addressing the problems of childhood and education, are seen as a powerful tool for shedding light on the social injustices of 19th-century England. Dickens’ own difficult childhood experiences deeply influenced his writing. Through his works, Dickens highlighted issues such as child labor, poverty, and the lack of education. In works like “Oliver Twist,” “David Copperfield,” and “Great Expectations,” Dickens fought to protect the rights of children and their right to education. His works encourage readers to think more about the rights of children and the necessity for them to receive a good education. Dickens’ works have not only influenced literature but also societal changes. His descriptions of the problems of childhood and education have helped raise social awareness and combat these issues.